IMPLEMENTASI TEKNIK CRAWLING UNTUK PENGUMPULAN DATA DARI MEDIA SOSIAL TWITTER - Saputra, Pramana Yoga (DINAMIKA DOTCOM, 2017)
Social media is an online communication network with millions of users. Users can interact with the other users, and share the information through the social media. The number of users and the high frequency of data traffic and data exchange, making social media into a data warehouse. Users can obtain valuable information from this data warehouse through the data collecting process, analysis and decision making. One of the techniques that used for collecting data is crawling. Crawling is the utilization of internet bot program to browse the addresses on the World Wide Web, to do indexing and to store important data in accordance with the purpose of the bot is made. In this research, we implementing crawling on Twitter. the reason why using Twitter, because Twitter is one of the biggest social media. There are approximately 700 million tweets per day, with an average of 7500 tweets per second from users around the world. Because of the amount of data stored in Twitter, the researcher chose Twitter, to implement crawling techniques in this study.Key word: crawling, social media, twitter